Intussusception of the third portion of the duodenum secondary to a primary duodenal malignancy: A case report. (May 2022) - Matsuura, Hirokazu; Saito, Akira; Amano, Yusuke; Morishima, Kazue; Sasanuma, Hideki; Lefor, Alan Kawarai; Sata, Naohiro
Abstract: Introduction and importance: Intussusception is invagination of the bowel and is rare in adults, representing only 5% of all cases of intussusception. Duodenal intussusception is also very rare. To the best of our knowledge, there is only one previous report of a malignant tumor in the fourth portion of the duodenum as the lead point of intussusception (Vaibhav et al., 2021 [1]). This reports a duodenal-duodenal intussusception caused by a malignant tumor in the third portion of the duodenum. Case presentation: A 36-year-old woman with abdominal pain was diagnosed with duodenal intussusception by abdominal ultrasonography and computed tomography scan. Double balloon endoscopy showed that the intussusception had spontaneously reduced, and a tumor was found in the third portion of the duodenum. Open resection was performed because of the tumor location. Pathologic examination revealed adenocarcinoma with an adenoma of the duodenum. The patient had no evidence of recurrence for 4 years after resection. Clinical discussion: This patient had a primary duodenal malignancy and presented with intussusception, Duodenal intussusception is a rare condition requiring prompt intervention, usually requiring surgery. In this patient, since endoscopic resection was difficult, partial resection of duodenum was performed by open surgery assisted by double balloon enteroscopy. The pathological diagnosis of the resected specimen was primary duodenal malignancy. Conclusion: This is a report of adult duodenal intussusception caused by a primary duodenal malignancy. This rare condition posed an intriguing challenge for the optimal operative approach. Highlights: Duodenal intussusception caused by a primary tumor is extremely rare. Intussusception is rare in adults. A duodenal tumor was identified with double balloon endoscopy and resected.